framework for delineating biogeographical regions based on species distributions - Kreft, Holger; Jetz, Walter (Journal of biogeography, 2010)
Biogeographical regionalizations, such as zoogeographical regions, floristic kingdoms or ecoregions, represent categorizations central to many basic and applied questions in biogeography, ecology, evolution and conservation. Traditionally established by experts based on qualitative evidence, the lack of transparency and quantitative support has set constraints on their utility. The recent availability of global species range maps, novel multivariate techniques and enhanced computational power now enable a quantitative scrutiny and extension of biogeographical regionalizations that will facilitate new and more rigorous uses. In this paper we develop and illustrate a methodological roadmap for species-level biogeographical regionalizations at the global scale and apply it to mammals. Global. We explore the relative usefulness of ordination and clustering methods and validation techniques. The performance of nine different clustering algorithms is tested at different taxonomic levels. The grain of regionalization (i.e. the number of clusters) will usually be driven by the purpose of the study, but we present several approaches that provide guidance. Non-metric multidimensional scaling offers a valuable first step in identifying and illustrating biogeographical transition zones. For the clustering of regions, the nine different hierarchical clustering methods varied greatly in utility, with UPGMA (unweighted pair-group method using arithmetic averages) agglomerative hierarchical clustering having consistently the best performance. The UPGMA approach allows a tree-like phenetic representation of the relative distances of regions and can be applied at different levels of taxonomic resolution. We find that the new quantitative biogeographical regions exhibit both striking similarities to and differences from the classic primary geographical divisions of the world's biota. Specifically, our results provide evidence that the Sahara, northern Africa, the Arabian Peninsula and parts of the Middle East should be regarded as part of the Afrotropics. Further, the position of the New Guinean continental shelf, Lydekker's Line, is supported as an appropriate border to separate the Oriental and Australian regions. We propose that this sort of new, quantitative delineation and relationship assessment across taxonomic and geographical grains is likely to offer opportunities for more rigorous inference in historical and ecological biogeography and conservation.